Task specialization and the Native-Foreign Wage Gap - Eduard Storm (LABOUR, 2022)
This study documents that worker-level variation in tasks has played a key role in the widening of the German Native-Foreign Wage Gap. I find idiosyncratic differences account for up to 34 per cent of the wage gap. Importantly, natives specialize in high-paying interactive activities not only between, but also within occupations. In contrast, foreign workers specialize in low-paying manual activities. This enhanced degree of task specialization accounts for 11 per cent of the gap among high-wage earners and 25 per cent among low-wage earner, thus offering new insight into sources for imperfect substitution of native and foreign workers and consequently small migration-induced wage effects.
Keywords: 380